A peak-to-average power ratio reduction method for mixed-numerology multi-carrier systems - Nan SHI; Xiaoran LIU; Jun XIONG; Xiaoying ZHANG; Jibo WEI (Dianxin kexue)
In order to support diverse service demands of communication scenarios, 5G adopts the mixed-numerology system based on orthogonal frequency division multiplexing (OFDM).The mixed-numerology systems still have the problem of high peak-to-average power ratio (PAPR).Furthermore, its design structure makes it difficult to apply traditional PAPR suppression methods straight forwardly, in which mixed signals are generated by superimposing multiple sub-signals with different parameters.An optimization model for minimizing PAPR in mixed-numerology systems was established based on tone reservation method.Utilizing the characteristic of single-peak of time-domain kernel, the multiple copies were generated in different numerologies based on the peak position of the mixed signal.The mixed time-domain kernel was then superimposed to reduce the peaks of the mixed signal.Since the proposed algorithm didn’t require inverse fast Fourier transform (IFFT)/ fast Fourier transform (FFT) operations during iteration, it had relatively low computational complexity.Simulation results show that the proposed algorithm effectively reduces the PAPR of mixed signals.